Card Match Circle (CMC) Media Assisted by 3D Models to Improve Fourth Grade Elementary Students’ Learning Outcomes on the Topic of Kingdoms in the Indonesian Archipelago - Putu Dita Karisma Yanti; Basilius Redan Werang; Ketut Herya Darma Utami (Universitas Pendidikan Ganesha, 2025)
The low level of students' understanding of Social Studies material has a direct impact on their poor learning outcomes. One contributing factor is the limited use of engaging and contextual learning media to support the learning process. This study aims to examine the validity, practicality, and effectiveness of the Card Match Circle (CMC) media assisted by 3D models in improving students' learning outcomes on the topic of Indonesian Kingdoms. This is a development research employing the ADDIE model, involving 2 material experts, 2 media experts, 1 teacher, and 14 fourth-grade students as research subjects. Data were collected using validation questionnaires, response questionnaires, and learning outcome tests. The data were analyzed quantitatively using a correlated t-test. The results showed that the CMC media assisted by 3D models had a very high validity level, with validation scores of 0.98 from material experts and 0.93 from media experts. The practicality of the media based on teacher responses reached 97.5% and student responses 86.1%, both categorized as very practical. Furthermore, the correlated t-test produced a significance value of 0.000 (p < 0.05), indicating that the media was effective in improving students' learning outcomes. The implication of this research highlights that integrating CMC media with 3D models offers an innovative alternative for active and interactive Social Studies learning to support students' competency achievement.